Abiotic stress responses in pulses: Impact of drought and high temperature - Rajmohan, A; Prasad, V Babu Rajendra; Senthil, A; Manivannan, N; Arul, L; Sumathi, A (Plant Science Today, 2025)
Pulses, a vital food crop in India, play a significant role in nutritional security and agriculture. Despite India's prominence in global pulse production, achieving self-sufficiency in pulse production is challenged by escalating drought and rising temperatures. This review examines the responses of pulse crops to drought and high temperatures, highlighting vulnerabilities that affect seed germination, growth, biomass and reproductive traits. Drought and heat stress adversely impact seed germination, vigor and biomass accumulation while altering root and shoot characteristics. Physiological responses, including changes in photosynthesis, nutrient absorption and oxidative damage are explored alongside the implications for root nodule development under water stress. Recent molecular studies identify specific genes and proteins linked to heat tolerance in various legumes, such as green gram, wild creole bean and chickpea. The roles of microRNAs and transcription factors in modulating heat stress responses are emphasized. Additionally, heat stress-induced differential gene expression in cowpea nodules and soybeans impacts flowering pathways and key regulatory genes. Understanding these complex interactions between environmental stressors and pulse crop physiology is crucial for developing resilient varieties and sustainable agricultural practices amid climate change-induced challenges. Future research should focus on elucidating the molecular mechanisms of drought and heat tolerance, particularly stress-responsive genes, transcription factors and microRNAs. Advances in gene editing and genomics will aid in creating resilient pulse varieties, while comparative studies can refine breeding strategies to enhance drought and heat tolerance, ultimately supporting sustainable pulse production.